The electrochemical behavior of copper and copper alloys as biomaterials - Žaklina Tasić; Milan Antonijević (Zaštita Materijala)
Different types of metals are used in the stomatology for dental applications. The oral environment is aggressive medium for metals and leads to corrosion. The metals undergo to chemical or electrochemical reactions in the oral environment which resulting in dissolution and formation of different chemical compounds. The present article reviews and discussed the electrochemical behavior of copper and copper alloys in synthetic saliva.